Analysis Of The Differences In Drug Procurement Via E-Catalog In The Years 2022 And 2023 At The Pharmacy Department Of X Hospital - Nina Rohdiana; Agusdini Banun Saptaningsih; Idrus Jus’at (Lembaga Pengembangan Kinerja Dosen, 2024)
Government policy changes and drug price fluctuations related to e-catalog can affect drug costs and types purchased between 2022 and 2023. This research aimed to analyze the differences in drug procurement using the e-catalog system and its interaction with hospital financial and operational variables. The study employed a mixed-methods approach to understand the dynamics of drug procurement at Pharmacy Department of X Hospital through the e-catalog system between 2022 and 2023. This research evaluated changes in purchasing volume, costs, cost efficiency, and service speed. Quantitative data were obtained from e-catalog documentation, focusing on the types, volumes, and prices of chronic medications, as well as BPJS claims. Statistical analysis was used to compare the study periods, while qualitative data from in-depth interviews with 15 respondents, observations and document analysis enriched the understanding of procurement process changes through data triangulation analysis. The results demonstrated an increased use of e-catalog, with policy changes leading to supplier diversification and price flexibility. Quantitative findings indicated a 25% increase in the volume of drug purchases through the e-catalog from 2022 to 2023, accompanied by a 15% reduction in average drug prices due to heightened competition among suppliers. Additionally, procurement efficiency improved by 30%, as reflected in the reduction of the procurement cycle time from 45 days to 31 days. These findings indicated shifting needs and procurement strategies, affecting budget efficiency and the speed of fulfilling drug requirements. In conclusion, strategic adaptations and ongoing evaluations in managing e-catalog are essential to address financial and logistical challenges, ensuring patient satisfaction and drug availability.